Examining risk behavior and risk management practices in oil and gas construction industry - Ahmad, Azira (2014)
The aim of this paper is to examine the risk behaviour and risk management practices among the employees in oil and gas construction industry. Risks are unpredictable events and activities which are known can be avoided and can also give positive or negative impacts to the events or activities. The impacts of these risks may contribute to the project’s objectives such as time, quality, cost and safety. Risk behaviour focuses on the role of an individual in the prevention of the risk to be happened. A risky behaviour leads to poor risk management practices and the organization performance as a whole. Risk management has long been associated with the use of market insurance to protect individuals and companies from various losses associated with accidents (Harrington and Neihaus, 2003). In 1990s, the governance of risk management become essential and integrated risk management was introduced. Data were obtained from 150 employees of Malaysia’s oil and gas construction’s company. The confirmatory factor analysis performed has identified five variables, namely risk behaviour (RB), risk management processes consist of risk identification (RI), risk analysis (RA), risk evaluation (RE) and risk treatment (RT) are good determinant factors of overall risk management practices (ORMP). The results are coherent with the findings by Kletz (1991), Jaffe (2001), Hammond (2002), Navare (2003), Nguyen et al. (2007) and Shama (2009). The findings also unveil the RI and RT does not have significant affect on ORMP.